Islamic Philanthropy Exploring Zakat, Waqf, and Sadaqah in Islamic Finance and Economics - Ismail, Abdul Ghafar; Abdullah, Rose; Zaenal, Muhammad Hasbi (Palgrave Studies in Islamic Banking, Finance, and Economics, 2022)
XXII, 350 p. 30 illus.